Peran Pendidikan untuk Membangun Jiwa Nasionalisme Siswa di SMAN 2 Sikakap Mentawai - Cici Nur Azizah; Pebriyenni Pebriyenni; Ridwan Ridwan (Journal of Moral and Civic Education, 2022)
Education has an important role in ensuring the survival of the nation and state. This is because education is a vehicle for building the quality of human resources. Therefore, this study was designed to describe the role of education in building the spirit of nationalism in students at SMA Negeri 2 Sikakap Mentawai. This study uses qualitative methods with data collection methods using observation, documentation and interview techniques. Data analysis was carried out in several stages, namely; inventorying and organizing data, carrying out the coding process, carrying out activities to describe data according to categories. The results of the study indicate that the problem that is still an obstacle for students to be able to carry out a proper education in the Mentawai is access to transportation which is still difficult. They have to travel long distances to get to school, so students are often late for school. In addition, the economic factor of the community which is still weak is also an obstacle for students to come to school. Because for them it is more important to earn a living than to go to school. And there is no awareness of the importance of education for them. Meanwhile, in terms of schools, good education must be carried out properly because through good education, the spirit of nationalism of students can be built well, meanwhile in practice schools find obstacles with student attendance times who often come late and challenges for teachers to be able to adjust learning. with the school environment and conditions that are still inadequate.